Alkali Metal Complexes: Mixed Ligand Complexes of Alkali Metal Salts of Some Organic Acids with Isonitrosoethylmethylketone. - PRAKASH, D.; KUMAR, B.; Prakash Gupta, Om (Asian Journal of Chemistry, 2010)
A number of mixed ligand complexes of alkali metal salts of o-nitrophenol, 2,4-dinitrophenol, 2,4,6-trinitrophenol, 1-nitroso-2-naphthol, salicylic acid, 8-hydroxyquinoline and o-aminobenzoic acid with isonitrosoethylmethylketone have been synthesised in absolute ethanol and characterised by elemental analysis, conductivity measurement and IR spectral data. Their IR spectral data indicate the presence of hydrogen bonding in them, which may be one of the dominant factors for their stability.